Physiological Roles of the Dual Phosphate Transporter Systems in Low and High Phosphate Conditions and in Capsule Maintenance of Streptococcus pneumoniae D39 - Zheng, Jiaqi J.; Sinha, Dhriti; Wayne, Kyle J.; Winkler, Malcolm E. (Frontiers in Cellular and Infection Microbiology, 2016)
Unlike most bacteria, Streptococcus pneumoniae (pneumococcus) has two evolutionarily distinct ABC transporters (Pst1 and Pst2) for inorganic phosphate (Pi) uptake. The genes encoding a two-component regulator (PnpRS) are located immediately upstream of the pst1 operon. Both the pst1 and pst2 operons encode putative PhoU-family regulators (PhoU1 and PhoU2) at their ends. This study addresses why S. pneumoniae contains dual Pi uptake systems and the regulation and contribution of the Pst1 and Pst2 systems in conditions of high (mM) Pi amount and low (μM) Pi amount. We show that in unencapsulated mutants, both pst1 and pst2 can be deleted, and Pi is taken up by a third Na+/Pi co-transporter, designated as NptA. In contrast, either pst1 or pst2 is unexpectedly required for the growth of capsule producing strains. We used a combination of mutational analysis, transcript level determinations by qRT-PCR and RNA-Seq, assays for cellular PnpR P amounts by SDS-PAGE, and pulse-Pi uptake experiments to study the regulation of Pi uptake. In high Pi medium, PhoU2 serves as the master negative regulator of Pst2 transporter function and PnpR P levels (post-transcriptionally). ΔphoU2 mutants have high PnpR P levels and induction of the pst1 operon, poor growth, and sensitivity to antibiotics, possibly due to high Pi accumulation. In low Pi medium, Pst2 is still active, but PnpR P amount and pst1 operon levels increase. Together, these results support a model in which pneumococcus maintains high Pi transport in high and low Pi conditions that is required for optimal capsule biosynthesis.